2019
DOI: 10.1080/10826084.2019.1673419
|View full text |Cite
|
Sign up to set email alerts
|

HIV Pre-exposure Prophylaxis for People Who Inject Drugs: The Context of Co-occurring Injection- and Sexual-Related HIV Risk in the U.S. Northeast

Abstract: Background: People who inject drugs (PWID) are at increased risk for HIV infection through sharing contaminated needles and injection equipment, and engaging in condomless sex.Objectives: To qualitatively examine the overlapping nature of these behaviors among PWID in the US Northeast. Methods:We recruited HIV-uninfected PWID and key informants through community-based organizations. Qualitative interviews explored sexual partnerships as they related to sharing CONTACT Alberto Edeza,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…We found that PWID perceive their own risk of HIV acquisition to be low, associating HIV risk not with drug use but rather with sexual risk, particularly that of MSM. This is consistent with prior studies [ 12 , 19 , 38 , 39 ] and reinforces the need to more carefully frame HIV alongside HCV as infections associated with injection drug use. Multiple studies have demonstrated the benefits of targeting HCV treatment among people with co-occurring HIV and HCV [ 40 42 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found that PWID perceive their own risk of HIV acquisition to be low, associating HIV risk not with drug use but rather with sexual risk, particularly that of MSM. This is consistent with prior studies [ 12 , 19 , 38 , 39 ] and reinforces the need to more carefully frame HIV alongside HCV as infections associated with injection drug use. Multiple studies have demonstrated the benefits of targeting HCV treatment among people with co-occurring HIV and HCV [ 40 42 ].…”
Section: Discussionsupporting
confidence: 90%
“…The US Centers for Disease Control and Prevention (CDC) published Clinical Practice Guidelines for PrEP in 2021 [9], which recommends PrEP patients visit their providers between two and four times annually for therapy maintenance. Evidence from prior work, however, reflects continued access issues for PWID in the context of high maintenance treatment programs such as the one recommended by CDC [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of stimulants such as methamphetamine, which is increasingly prevalent among social networks of cisgender men who have sex with men (MSM) [4], is associated with heightened impulsivity, behavioral disinhibition, engagement in condomless anal or vaginal sex, and multiple sexual partnerships [5]. Numerous studies have also consistently shown that PWUD are more prone to engaging in behaviors that can transmit HIV, such as having condomless sex and sharing syringes for drug injection [6,7]. In fact, data from the U.S National Behavioral Surveillance Survey reveals that approximately three-quarters of sampled people who inject drugs (PWID) reported engaging in receptive syringe sharing and/or condomless sex in the past year [8].…”
Section: Introductionmentioning
confidence: 99%
“…Of those, about 1.6 million PWID (13%) are living with HIV and nearly 6 million PWID (50%) are living with hepatitis C virus (HCV) (UN World Drug Report, 2017). PWID are at increased risk for acquiring these viral blood borne infections as well as bacterial infections, such as infective endocarditis, due to a variety of risk factors, including injection and sexual risk behaviors (Broz et al, 2014;Edeza et al, 2020;Neaigus et al, 2013). High-risk injection behaviors include reusing syringes, sharing needles/syringes and drug preparation equipment, and using nonsterile injection supplies; and high risk sexual behavior includes multiple sexual partners, transactional sex, condomless sex, and condomless anal sex (Bogart et al, 2005).…”
Section: Introductionmentioning
confidence: 99%